Analysis of Rice Farmer Problems in Improving Community Welfare in Kelurahan Cengkeh Turi Kota Binjai - Ela Rizky Wardhani; Rahmad Sembiring (MultiTech Publisher, 2024)
Indonesia's rice sector was once self-sufficient due to government support, macroeconomic policies, and technological advancements like the Green Revolution in lowland rice cultivation. However, the Cengkeh Turi sub-district in Binjai City, North Sumatra, faces welfare issues such as lack of capital, polluted soil, uncertain rice prices, limited land area, poor quality seeds, plant pests, lack of human resources, and a lack of government involvement in agriculture. This research aims to analyze factors such as seed type, fertilizer type, labor, land conversion, capital, distribution, and climate to improve the welfare of farmers in Cengkeh Turi Village. Data processing using Confirmatory Factor Analysis (CFA) and Multiple Linear Regression was used. Results showed that distribution, climate, labor, and land use change factors significantly impact the welfare of the community in Cengkeh Turi Village, while the type of seed and fertilizer type had a positive effect on the welfare of the community in Kelurana Cengkeh Turi. The study highlights the need for improved agricultural practices and government support to improve the welfare of farmers in Cengkeh Turi Village.